PENGINDRAAN KAPITAL INTENSITAS, ARUS KAS, DAN TINGKAT AKTIVITAS DALAM MEMPREDIKSI KESULITAN KEUANGAN - Diva Tirta Nirwana Rahmadetta; Shinta Permata Sari; Suhesti Ningsih (ITB AAS INDONESIA, 2024)
Financial difficulties are an early symptom before bankruptcy occurs. Almost all companies in Indonesia avoid this condition by anticipating this symptom within and outside the company. This research aims to determine the effect of capital intensity, cash flow, and activity on financial distress in non-cyclical consumer sector companies for the 2020-2022 period. This research is a type of quantitative research using secondary data, namely the company’s audited financial statement that present in the annual report. The sampling technique used is a purposive sampling technique with a sample size of 119 data during 2020-2022 period. The data analysis used in this research is multiple linier regression analysis. The research result show that cash flow and activity influence financial distress. Meanwhile, capital intensity has no effect on financial distress.